Validation of a guidance material for primary caregivers on child health care: Pereira Rossell Hospital Center, Uruguay 2024 (Archives of Pediatrics of Uruguay, 2025)
Introduction: in 2023, professors from the Academic Unit of Pediatrics C, School of Medicine, developed informative material on relevant health topics.Objectives: validate this material aimed at primary caregivers of hospitalized children at the Pereira Rossell Hospital Center.Methodology: cross-sectional observational study that included primary caregivers over 18 years old of hospitalized children and adolescents from July to September 2024. Participants evaluated the material in terms of attractiveness, acceptance, understanding, identification, and inducement to change through closed (dichotomous and Likert scale) and open-ended questions.Results: 220 interviews were conducted. The median age of caregivers was 30 years; 198 (90%) were women and 176 (80%) were mothers. 215 (98%) found the material interesting, and 179 (81.4%) considered it likely to read on their own. Researchers interpreted that 90.9% of the participants’ expressions aligned with the message. Caregivers understood the message in 92.7% of cases and 191 (86.8%) considered the situation presented in the material as likely. Additionally, 40% mentioned that it was very likely that this material would modify their actions.Conclusions: the results showed that the majority, meeting the objectives based on the five criteria used, approved the validated educational material. Feedback during the validation process identified areas for improvement, providing a solid foundation for future research and enhancements in educational material, aiming to promote optimal health practices and improve the quality of childcare.
Keywords: Child Care; Caregivers